QSPR ANALYSIS OF A SET OF LIQUID CRYSTALS IN THE BENZYLIDENEANILINE CLASS ACCORDING TO THEIR TRANSITION TEMPERATURE - DIPPONG, Thomas; AVRAM, Alexandra; GOGA, Firuța (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The present paper focuses on the connection amongst the structure of 25 liquid crystals in the benzylideneaniline class and some of their physico-chemical properties. Simple and multiple correlations between transition temperatures and 34 calculated molecular descriptors (25 topological indices and 12 Van der Waals parameters), for each compound, were made. Simple and multiple correlations amongst topological indices and Van der Waals parameters, respectively, observing the variations taking place, are presented.